Clinical practice guidelines : - Wesorick, Bonnie (Practice Field Publishing, 2000)
This book provides evidence-based tools and resources to help you prepare for, and enhance your learning and enjoyment of clinical practice. The clinical tools, clinical practice guidelines and education outcome records support both the art and science of nursing.